2003
DOI: 10.1159/000073229
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Elevated Levels of Insulin-Like Growth Factor-Binding Protein-2 as Indicators of Hepatocellular Carcinoma

Abstract: Background/Aims: Insulin-like growth factor-binding protein-2 (IGFBP-2) is expressed in many malignant tissues, and elevated serum levels can be indicators of tumour activity in addition to conventional tumour markers. Our aim was to evaluate the role of IGFBP-2 levels together with insulin-like growth factor (IGF)-I, IGF-II and IGFBP-3 in the diagnostic work-up of patients with hepatocellular carcinoma (HCC). Methods: In 50 (39 males, 11 females) histologically confirmed and TNM-graded patients with HCC who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 31 publications
3
38
0
Order By: Relevance
“…By contrast, serum IGFBP-2 was significantly elevated in HCC patients regardless of cirrhosis status, being 5-fold higher than in healthy controls ( Table 2). Our observation is in excellent agreement with earlier findings by Ranke et al, who in 50 HCC patients observed an increase in IGFBP-2 of similar magnitude, irrespective of the presence or absence of cirrhosis [36]. In conjunction, the two studies suggest that IGFBP-2 may serve as a marker of HCC, but only among patients without liver cirrhosis, as patients with cirrhosis but without HCC had even higher IGFBP-2 levels.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, serum IGFBP-2 was significantly elevated in HCC patients regardless of cirrhosis status, being 5-fold higher than in healthy controls ( Table 2). Our observation is in excellent agreement with earlier findings by Ranke et al, who in 50 HCC patients observed an increase in IGFBP-2 of similar magnitude, irrespective of the presence or absence of cirrhosis [36]. In conjunction, the two studies suggest that IGFBP-2 may serve as a marker of HCC, but only among patients without liver cirrhosis, as patients with cirrhosis but without HCC had even higher IGFBP-2 levels.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, serum levels of IGFBP-2 showed significant increase in both diabetic and non-diabetic HCC patients. These data are in accordance with previous reports indicating that serum levels of IGFBP-2 were significantly higher while IGFBP-3 levels were normal [36] or significantly lower [37] in patients with HCC compared to healthy subjects.…”
Section: Discussionsupporting
confidence: 93%
“…It acts not only as carrier of IGFs, prolonging their half-life, but also functions as modulator of IGF availability and activity. IGFBP-2 is over-expressed in ovarian [15], colorectal [16], prostate [17,18], hepatocellular carcinomas [19] and in neuroblastoma [20]. It has also been demonstrated that IGFBP-2 over-expression might promote glioma development and progression [21] and enhance GB invasion [22].…”
Section: Discussionmentioning
confidence: 99%